Policing domestic violence: perceptions, experience, and reality - Friday, Paul C. (Criminal justice review, 1991)
This research explores police attitudes and experiences with a departmental policy favoring arrest in cases of domestic violence. It also addresses the impact that such a policy may have on future domestic violence calls. Analyses were based on two data sets: a calls and arrests recorded for two years prior to the implementation of an arrest policy and for two years after and b a survey of patrol and command officers. This is a study of the impact of an arrest policy on the police; it is not a study of domestic violence per se. The findings reflect "normal police operations."Survey data suggest that officers strongly supported both the law permitting spouse arrest and the departmental policy, because it gave them more power, but that they were uncertain of the actual impact on their own return calls and on the victims. The statistical data reveal that arrest minimally impacted the number of subsequent calls; the vast majority of calls resulted in no callbacks whether an arrest was made or not. In looking at prior contact with the police for domestic violence, the impact of arrest was more evident. The greatest impact of arrest was seen on those who had had no prior contacts. The largest proportion of callbacks involved offenders who had prior records for domestic violence and who were not arrested, and the lowest proportion involved offenders with no priors who were arrested.Prior police contacts with victims were also reviewed, revealing that a small but significant proportion of victims had had drunk and disorderly charges, whereas perpetrators showed a high number of contacts for both disorderly and other criminal behaviors. Police experience with these cases has tended to create a selective generalization regarding the nature of domestic violence and the impact of the policy